Solitary Calcified Nodules as the Cause of Carpal Tunnel Syndrome: Two Case Reports and Literature Reviews - Cheng, Ting-Feng; Chen, Chun-Yu; Liu, Ping-Tang; Yang, Shan-Wei (Frontiers in Neurology, 2019)
Solitary calcified nodule-related carpal tunnel syndrome (CTS) is rare and easy to be misdiagnosed owing to the high incidence of primary CTS. Release of the transverse carpal ligament without removal of the mass leads to persistence of the symptoms and subsequent complications like wasting of the thenar muscles. Here, we report two cases of solitary calcified nodule-related CTS and discuss the role of ultrasound in preventing misdiagnosis. Both patients reported persistent numbness over the lateral side of their palm and weakness of the right wrist with thenar muscle atrophy. One patient had undergone transverse carpal ligament release 2 years previously, and the other had received a local injection of lidocaine at the clinic. Neither patient experienced symptom relief. X-ray revealed a similar finding of nodule lesions in front of the capitate–hamate region. Solitary calcified nodule-related CTS was diagnosed, and the patients underwent nodule removal with/without transverse ligament release. The first patient was a typical case of misdiagnosed solitary calcified nodule-related CTS. The second patient had a definitive clinical sonographic diagnosis before surgery. The accurate diagnosis of secondary CTS is paramount for performing effective surgery. Thus, ultrasonography is an easy, convenient, safe, and effective method in screening for secondary CTS.